Reward Design for Customer Referral Programs: Reward–Product Congruence Effect and Gender Difference - Hu, Hai-hua; Zhang, Xin-Mu (Frontiers in Psychology, 2021)
Referral reward design is the core component of customer referral programs (CRPs), which are often applied to recruit new customers. This research aims to compare the effectiveness of utilitarian versus hedonic rewards, both of which are widely used in CRPs, in referral generation. Through a field study and two laboratory studies, we demonstrate a reward–product congruency effect; that is, utilitarian rewards, compared with hedonic rewards, yield a higher referral likelihood for utilitarian products, while the opposite holds true for hedonic products. In some cases, however, such a congruency effect would be crippled by gender segmentation. When males make referral decisions towards hedonic products, the effectiveness of utilitarian rewards is at least equal to that of hedonic rewards. When females make referral decisions towards utilitarian products, there is no difference in effectiveness between utilitarian and hedonic rewards. These findings provide novel insights into referral reward design.